Determination of the Local Electric Field at Au/SAM Interfaces Using the Vibrational Stark Effect - Staffa, Jana K. (2017)
A comprehensive understanding of physical and chemical processes at biological membranes requires the knowledge of the interfacial electric field which is a key parameter for controlling molecular structures and reaction dynamics. An appropriate approach is based on the vibrational Stark effect (VSE) that exploits the electric-field dependent perturbation of localized vibrational modes. In this work, 6-mercaptohexanenitrile (C5CN) and 7-mercaptoheptanenitrile (C6CN) were used to form self-assembled monolayers (SAMs) on a nanostructured Au electrode as a simple mimic for biomembranes. The C - N stretching mode was probed by surface enhanced infrared absorption (SEIRA) spectroscopy to determine the frequency and intensity as a function of the electrode potential. The intensity variations were related to potential-dependent changes of the nitrile orientation with respect to the electric field. Supported by electrochemical impedance spectroscopy, molecular dynamics simulations, and quantum chemical calculations the frequency changes were translated into profiles of the interfacial electric field, affording field strengths up to 4 × 108 V/m (C6CN) and 1.3 × 109 V/m (C5CN) between +0.4 and 0.4 V (vs Ag/AgCl). These profiles compare very well with the predictions of a simple electrostatic model developed in this work. This model is shown to be applicable to different types of electrode/SAM systems and allows for a quick estimate of interfacial electric fields. Finally, the implications for electric-field dependent processes at biomembranes are discussed.